2017
DOI: 10.1007/s10803-017-3112-6
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of a Behavioral Parent Training in the Republic of Macedonia

Abstract: Parenting children with autism in countries with limited professional and financial resources can be overwhelming. Parent training led by non-governmental organizations may help alleviate some of these burdens. The present pilot study was conducted in the Republic of Macedonia, a country located in Southeastern Europe. The purpose of the study was to evaluate a parent training model for disseminating evidence-based practices through didactic and pyramidal training strategies. Results indicated that children im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 42 publications
0
14
0
1
Order By: Relevance
“…Parent training among families was used in four studies: Bruder and Bricker (1985), Neef (1995), Hansen et al (2017), and Conklin and Wallace (2019). Through this approach, the programs were able to reach more families and more children.…”
Section: Overview Of the Studies And Demographicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Parent training among families was used in four studies: Bruder and Bricker (1985), Neef (1995), Hansen et al (2017), and Conklin and Wallace (2019). Through this approach, the programs were able to reach more families and more children.…”
Section: Overview Of the Studies And Demographicsmentioning
confidence: 99%
“…On the other hand, the information about the second and third level of trainings was presented with varying degrees of detail. In some cases, the authors only indicated that the parents used the same training approach as the master trainer (Loughrey et al, 2014;Hansen et al, 2017;Knecht, 2018;Conklin & Wallace, 2019). In other instances, it was up to the parent to decide on the training methods and timeframe (Adubato et al, 1981;Symon, 2005) when training the next level of parents or caregivers.…”
Section: Training Fidelitymentioning
confidence: 99%
See 1 more Smart Citation
“…O uso de programas de treinamento online, como o OASIS, e de estratégias de ensino computadorizadas, online ou por telecomunicação indicam que as pesquisas na área têm buscado formas de capacitar pais ou cuidadores à distância, por meio de estratégias computadorizadas. No treinamento piramidal, o terapeuta treina um pai ou cuidador e este treina outro pai ou cuidador, de modo a maximizar o alcance e disseminar a intervenção (HANSEN et al, 2017). A necessidade de criar formas de intervenção que garantam o acesso de um maior número de indivíduos a ela e que facilitem a participação de indivíduos que residem em áreas mais remotas pode ser um impulsionador para mais pesquisas que explorem estratégias computadorizadas ou de treinos piramidais.…”
Section: Eat-up (Muldoon; Cosbey 2018)unclassified
“…However, PE in autism is not accessible by all and is limited or unavailable in many regions, including south‐east Europe (Daniels et al ., 2017; Hansen et al ., 2017). A three‐year European Commission‐funded project, Equity and Social Inclusion through Positive Parenting (ESIPP), was established in 2015 to address this shortfall for families in Croatia, Cyprus and North Macedonia.…”
Section: Introduction: Parent Education In Autism and The Esipp Projectmentioning
confidence: 99%